IMPLEMENTATION OF MARKETING MIX AT KHANSA FOOD DURING THE COVID-19 PANDEMIC - Utami, Sri Sari; Widowati, Rahayu (Politeknik Kelautan dan Perikanan Sidoarjo, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy by raising the economic level of the general public, alleviating poverty, and earning foreign exchange for the country. The Covid 19 pandemic has had a significant economic impact in Indonesia. Khansa Food has been able to survive and rise from the midst of the Covid 19 pandemic by utilizing the resources available to them. The implementation of the marketing mix strategy at Khansa Food is critical to the company's long-term viability. The right marketing mix combination is a means to maintain, expand, and increase company profits. The objective of this study was to determine how the marketing mix was implemented at Khansa Food. The descriptive qualitative research method was used, with primary and secondary data. The study's findings that Khansa Food's combination of product, price, location, and promotion is well-defined. Khansa Food's products are of high quality and are standardized. Prices are kept competitive, and customers can purchase products either online or in-store. Online promotions and various exhibitions have been programmed. There is always room for improvement to boost business performance. According to the research findings, online sales can be increased in order to reach a larger market. Increased online promotion via social media can be used as a low-cost alternative promotion. Manufacturers must adapt to online promotions and sales due to changes in consumer behavior toward online transactions. The enhancements are expected to benefit Khansa Food's business in both the short and long term.